1996
DOI: 10.1577/1548-8675(1996)016<0241:davoai>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Index of Biotic Integrity for Coldwater Streams in Wisconsin

Abstract: The index of biotic integrity (IBI). developed from information on the structure, composition, and functional organization of fish assemblages, is used to assess the health of aquatic ecosystems. We analyzed two large statewide data sets on stream fish assemblages to develop and test a version of the IBI for application to Wisconsin coldwater streams (maximum daily mean water temperature usually <22°C). This new IBI is needed because fish assemblages in Wisconsin coldwater streams differ significantly from tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
203
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(208 citation statements)
references
References 27 publications
3
203
1
1
Order By: Relevance
“…Hughes et al (1998) and Mebane et al (2003) reported that their IBIs had greater among-site versus within-site variability (signal/noise) than the metrics forming them. But Hughes et al (2004) and Whittier et al (Lyons et al 1996;Mundahl and Simon 1999;Ferreira et al 2007;Whittier et al 2007). However, predictive IBI modeling (which calibrates for natural gradients in size, temperature, and elevation) does not necessarily require separation into warmwater and coldwater models (Oberdorff et al 2002;Pont et al 2006Pont et al , 2009.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hughes et al (1998) and Mebane et al (2003) reported that their IBIs had greater among-site versus within-site variability (signal/noise) than the metrics forming them. But Hughes et al (2004) and Whittier et al (Lyons et al 1996;Mundahl and Simon 1999;Ferreira et al 2007;Whittier et al 2007). However, predictive IBI modeling (which calibrates for natural gradients in size, temperature, and elevation) does not necessarily require separation into warmwater and coldwater models (Oberdorff et al 2002;Pont et al 2006Pont et al , 2009.…”
Section: Discussionmentioning
confidence: 97%
“…The IBI of Oliveira and Ferreira (2002) has two metrics (percent native individuals and percent tolerant individuals) that will reduce IBI scores with increased numbers of tolerant nonnative game fish species (higher FQI scores). Lyons et al (1996) noted that an IBI score does not indicate fishery quality because stocked fish in Wisconsin streams may yield high quality fisheries, despite having low or intermediate IBI scores. Whittier et al (1997) reported that piscivores, especially nonnative piscivores introduced to improve fishing, were associated with lower minnow species richness (lower IBI scores) in northeastern U.S. lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Fish Index of Biotic Integrity and fish richness studies indicated slight improvement at several SMCW sites. The slimy sculpin (Cottus cognatus) was also first found in 2001, which was a further positive development because this fish is classified as intolerant of environmental degradation and as a stenothermal cold water species (Lyons et al 1996;Mundahl and Simon 1999). The slimy sculpin was the dominant fish species found at the Bloody Run Creek site during each annual assessment and accounted for 95% of the fish population during six of the ten years.…”
Section: Resultsmentioning
confidence: 99%
“…While not unexpected, the result is highly relevant to implementation of biological monitoring based on fish. In most IBI's, the typical response of native species to degradation is a reduction in species richness (coldwater stream IBI provides a notable exception (Lyons et al 1996)). However, the game fishes in this study are native, and undergo an increase in richness at low to moderate levels of human impact.…”
Section: Connectedmentioning
confidence: 99%